Development of an miRNA-Array-Based Diagnostic Signature for Periodontitis - Jin, Su-Han; Zhou, Jian-Guo; Guan, Xiao-Yan; Bai, Guo-Hui; Liu, Jian-Guo; Chen, Liang-Wen (Frontiers in Genetics, 2020)
Periodontitis progression is accompanied by irreversible alveolar bone absorption and leads to tooth loss. Early diagnosis is important for tooth stability and periodontal tissue preservation. However, there is no recognized miRNA diagnostic signature with convincing sensitivity and specificity for periodontitis. In this study, we obtained miRNA-array expression profiles of periodontitis from the Gene Expression Omnibus database. After screening for differentially expressed miRNAs, the least absolute shrinkage and selection operator (LASSO) method was performed to identify and construct a 17 miRNAs-based diagnostic signature (hsa-miR-3917, hsa-mir-4271, hsa-miR-3156, hsa-miR-3141, hsa-miR-1246, hsa-miR-125a-5p, hsa-miR-671-5p, hcmv-mir-UL70, hsa-miR-650, hsa-miR-497-3p, hsa-miR-145-3p, hsa-miR-141-3p, hsa-miR-210-3p, hsa-miR-204-3p, hsa-miR-203a-5p, hsa-miR-99a-3p, and hsa-miR-30a-3p). Periodontal tissue samples with higher risk scores were more likely to show symptoms of periodontitis. Then, the receiver operating characteristic (ROC) curves were used to assess the diagnostic value of the miRNA signature, which indicated that the optimum cut-off value in periodontitis diagnosis was 0.5056 with an area under the ROC curve (AUC) of 0.996, sensitivity of 97.3%, specificity of 100.0% in the training cohort; and the AUC 0.998, sensitivity of 97.9%, specificity of 91.7% in the testing cohort. We next evaluated the efficacy of the signature in differentiating disease subtype and affected range. Furthermore, we conducted functional enrichment analysis of the 17 miRNAs targeted mRNAs, including the regulation of mTOR activity and cells autophagy, Th1/Th2 cell balance and immunoregulation, cell apoptosis, and so on. In summary, our study identified and validated a 17-miRNA diagnostic signature with convincing AUC, sensitivity, and specificity for periodontitis.